Isolation of bacteriophages to multi-drug resistant Enterococci obtained from diabetic foot: A novel antimicrobial agent waiting in the shelf? - C S Vinodkumar; H Srinivasa; K G Basavarajappa; S Geethalakshmi; Nitin Bandekar (Wolters Kluwer Medknow Publications, 2011)
Introduction: While foot infections in persons with diabetes are initially treated empirically, therapy directed at known causative organisms may improve the outcome. Many studies have reported on the bacteriology of diabetic foot infections (DFIs), but the results have varied and have often been contradictory. The purpose of the research work is to call attention to a frightening twist in the antibiotic-resistant Enterococci problem in diabetic foot that has not received adequate attention from the medical fraternity and also the pharmaceutical pipeline for new antibiotics is drying up. Materials and Methods: Adult diabetic patients admitted for lower extremity infections from July 2008 to December 2009 in the medical wards and intensive care unit of medical teaching hospitals were included in the study. The extent of the lower extremity infection on admission was assessed based on Wagner's classification from grades I to V. Specimens were collected from the lesions upon admission prior to the initiation of antibiotic therapy or within the first 48 h of admission. Results: During the 18-month prospective study, 32 strains of Enterococcus spp. (26 Enterococcus faecalis and 06 E. faecium) were recovered. Antibiotic sensitivity testing was done by Kirby-Bauer's disk diffusion method. Isolates were screened for high-level aminoglycoside resistance (HLAR). A total of 65.6% of Enterococcus species showed HLAR. Multidrug resistance and concomitant resistance of HLAR strains to other antibiotics were quite high. None of the Enterococcus species was resistant to vancomycin. Conclusion: Multidrug-resistant Enterococci are a real problem and continuous surveillance is necessary. Today, resistance has rendered most of the original antibiotics obsolete for many infections, mandating the development of alternative anti-infection modalities. One of such alternatives stemming up from an old idea is the bacteriophage therapy. In the present study, we could able to demonstrate the viable phages against MDR E. faecalis.